Hanghaus 2 in Ephesos. Die Wohneinheit 6. Tafelband Baubefund, Ausstattung, Funde - Thür, Hilke (Verlag der Österreichischen Akademie der Wissenschaften, 2014)
The Imperial Period Dwelling WE 6 of Terrace House 2 in Ephesus. Living invironment of a family of the town elite.